Inflammatory cytokine biomarkers of asymptomatic sexually transmitted infections and vaginal dysbiosis: a multicentre validation study. (17th July 2018) - Masson, Lindi; Barnabas, Shaun; Deese, Jennifer; Lennard, Katie; Dabee, Smritee; Gamieldien, Hoyam; Jaumdally, Shameem Z; Williamson, Anna-Lise; Little, Francesca; Van Damme, Lut; Ahmed, Khatija; Crucitti, Tania; et al.
Abstract : Objectives: Vaginal dysbiosis and STIs are important drivers of the HIV epidemic and reproductive complications. These conditions remain prevalent, partly because most cases are asymptomatic. We have shown that inflammatory cytokines interleukin (IL)-1α, IL-1β and interferon-γ-induced protein (IP)-10 are biomarkers for detecting asymptomatic STIs and vaginal dysbiosis (bacterial vaginosis (BV) or intermediate microbiota). This study aimed to validate the performance of these biomarkers in African women recruited regardless of symptoms. Methods: IL-1α, IL-1β and IP-10 were measured in menstrual cup secretions, endocervical, lateral vaginal wall and vulvovaginal swabs from 550 women from Pretoria, Soweto and Cape Town, South Africa and Bondo, Kenya using Luminex and ELISA. STIs were assessed by PCR, BV by Nugent scoring and vaginal microbiota by 16S rRNA sequencing. Results: Across four study populations and four types of genital specimens, the performance of IL-1α, IL-1β and IP-10 for identification of women with STIs, BV or intermediate microbiota was consistent. Of the genital samples assessed, biomarkers measured in lateral vaginal wall swabs performed best, correctly classifying 76%(95% CI 70% to 81%) of women according to STI, BV or intermediate microbiota status (sensitivity 77%, specificity 71%) and were more accurate than clinical symptoms (sensitivity 41%, specificity 57%) (p=0.0003). Women incorrectly classified as STI/BV positive using the biomarkers had more abundant dysbiosis-associated bacteria, including Prevotella bivia and Gardnerella sp, detected by 16S rRNA sequencing, but not Nugent scoring. Including vaginal pH with the cytokine biomarkers improved the accuracy of the test (82% (95% CI 75% to 88%) correctly classified), although pH alone had poor specificity (61%). Conclusions: An inexpensive, point-of-care screening test including IL-1α, IL-1β and IP-10 (and potentially pH) could be used in resource-limited settings to identify women with asymptomatic STIs and dysbiosis. These women could then be referred for aetiological testing, followed by specific treatment.